PERTUMBUHAN BIBIT KAKAO (Teobroma cacao L) DENGAN BERBAGAI PEMBERIAN DOSIS SERBUK GERGAJI PADA VARIETAS (BUNDO-F1) DI TANAH GAMBUT - YOYON RIONO (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2020)
This study aims to determine the growth of cacao seeds (Teobroma cacao L) with various doses of sawdust on Vairietas (Bundo-F1) on peat lands. This research has been carried out in the experimental garden of the Faculty of Agriculture, Islamic University of Indragiri Tembilahan, Tembilahan Hulu Subdistrict, Indragiri Downstream District. When the study began from April to July 2019 this research was a field trial using a non-factorial randomized block design (RBD) consisting of 6 levels, namely M0 = peat only, M1 = 1: 1 (sawdust: peat), M2 = 2 : 1 (sawdust: peat), M3 = 3: 1 (sawdust: peat). Each treatment was repeated three times to obtain 18 experimental trial plots in the field. Data from this study were analyzed using Analysis of Variance (ANOVA). The results showed that the treatment of M2 = 2: 1 (sawdust: peat) could have a significant effect on plant height (cm), stem diameter (mm), number of leaves (strands),